Pervasive Health Knowledge Management - Mohd Khanapi, Abd Ghani (Springer, 2013)
Between rising costs and decreasing accessibility, the present health care picture is fraught with shortcomings—a discouraging scenario for the millions of patients struggling with chronic diseases such as diabetes and hypertension. In response, computer technology is emerging as a key factor in the transition from inefficient centralized health systems toward patient-centered, patient-involved care: pervasive healthcare.